2015
DOI: 10.1002/lary.25200
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal organized Hematoma: Clinical features of seventeen cases and a systematic review

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
87
7
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(113 citation statements)
references
References 17 publications
3
87
7
9
Order By: Relevance
“…The age distribution of OH patients shows a bimodal peak in teenagers and those over 70. It is interesting that a high prevalence of OHs occurred in teenagers in this study compared to other studies (6) . Several reports have suggested that OHs occur at a younger age (2,3,13,14,(16)(17)(18)(19)(20) .…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…The age distribution of OH patients shows a bimodal peak in teenagers and those over 70. It is interesting that a high prevalence of OHs occurred in teenagers in this study compared to other studies (6) . Several reports have suggested that OHs occur at a younger age (2,3,13,14,(16)(17)(18)(19)(20) .…”
Section: Discussioncontrasting
confidence: 39%
“…This disease has had many names, including "organizing hematoma, " "organized hematoma, " "hematoma of the maxillary sinus, " "hemorrhagic pseudotumor, " and "maxillary sinus hematoma" (2)(3)(4)(5) . ted that 39.7% of patients exhibited bony destruction (6) . This characteristic can lead to an incorrect preoperative diagnosis of malignant tumor (7) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it has been reported previously that cases of OHMS have benign clinical manifestations and do not recur or present with further complications after complete surgical evacuation. [3][4][5][6][7][8][9] Herein, we report a case of OHMS which was complicated by facial and orbital abscesses. The OHMS showed marked enlargement and extensive bone destruction that had occurred during an 8-month period.…”
mentioning
confidence: 99%